α2-Adrenergic Disruption of β Cell BDNF-TrkB Receptor Tyrosine Kinase Signaling - Kalwat, Michael A.; Huang, Zhimin; Binns, Derk D.; McGlynn, Kathleen; Cobb, Melanie H. (Frontiers in Cell and Developmental Biology, 2020)
Adrenergic signaling is a well-known input into pancreatic islet function. Specifically, the insulin-secreting islet β cell expresses the Gi/o-linked α2-adrenergic receptor, which upon activation suppresses insulin secretion. The use of adrenergic agonist epinephrine at micromolar doses may have supraphysiological effects. We found that pretreating β cells with micromolar concentrations of epinephrine differentially inhibited activation of receptor tyrosine kinases. We chose TrkB as an example because of its relative sensitivity to the effects of epinephrine and due to its potential regulatory role in the β cell. Our characterization of brain-derived neurotrophic factor (BDNF)-TrkB signaling in MIN6 β cells showed that TrkB is activated by BDNF as expected, leading to canonical TrkB autophosphorylation and subsequent downstream signaling, as well as chronic effects on β cell growth. Micromolar, but not nanomolar, concentrations of epinephrine blocked BDNF-induced TrkB autophosphorylation and downstream mitogen-activated protein kinase pathway activation, suggesting an inhibitory phenomenon at the receptor level. We determined epinephrine-mediated inhibition of TrkB activation to be Gi/o-dependent using pertussis toxin, arguing against an off-target effect of high dose epinephrine. Published data suggested that inhibition of potassium channels or phosphoinositide-3-kinase signaling may abrogate the negative effects of epinephrine, however these did not rescue TrkB signaling in our experiments. Taken together, these results show that 1) TrkB kinase signaling occurs in β cells and 2) use of epinephrine in studies of insulin secretion requires careful consideration of concentration-dependent effects. BDNF-TrkB signaling in β cells may underlie pro-survival or growth signaling and warrants further study.